SELECTION FOR HIGHER THREE WEEK BODY WEIGHT IN JAPANESE QUAIL:2. ESTIMATION OF GENETIC PARAMETERS - J. Hussain; M. Akram; A. W. Sahota; K. Javed; H. A. Ahmad; S. Mehmood; A. S. Jatoi; S. Ahmad (Journal of Animal and Plant Sciences, 2014)
Data on pedigree and performance records of 480 Japanese quails progeny of 81 sires and 200 dams maintained at Avian Research and Training Centre, University of Veterinary and Animal Sciences, Lahore selected for three generations for higher body weight were used to estimate some genetic parameters for body weight, egg production performance, egg quality and hatching traits. The generation, sex and genetic groups were included as fixed effects in the model for univariate analysis through WOMBAT computer software for Restricted Maximum Likelihood (REML) procedure. The heritability estimates of body weight at the age of 3rd, 4th and 6th weeks were 0.0126, 0.0315 and 0.20, respectively. For egg production traits including age at 1st egg, total eggs produced and average feed consumed per egg, heritability estimates were 0.20, 0.20 and 0.0047, respectively. Whereas for fertility and clear eggs %, heritability estimates were almost negligible indicating the impact of environment more pronounced than genetics on hatching traits. Breeding values for growth performance in selected birds at the age of three weeks ranged between, -0.1845 to 0.4102, -0.2309 to 0.471 and -0.0908 to 0.5373 in generation 1, 2 and 3, respectively. For random-bred control birds the values ranged between -0.845 to 0.6384, -1.2542 to 0.6713 and -1.3781 to 0.7623 for 1st, 2nd and 3rd generation, respectively. Genetic trend lines indicated positive response to selection as the generations progressed.
Keywords: Japanese quail; selection; body weight; heritability; breeding values; genetic trend